2013
DOI: 10.1262/jrd.2012-137
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern Implicates a Potential Role for Luman Recruitment Factor in the Process of Implantation in Uteri and Development of Preimplantation Embryos in Mice

Abstract: Luman/CREB3 recruitment factor (LRF or CREBRF) was identified as a regulator of Luman (or CREB3) that is involved in the unfolded protein response during endoplasmic reticulum stress. Luman is implicated in a multitude of functions ranging from viral infection and immunity to cancer. The biological function of LRF, however, is unknown. In this paper, we report that uteri of pregnant mice and embryos displayed enhanced LRF expression at all stages, and the expressed LRF was found to be localized specifically at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Localization of Cx43 and Cx37 was confirmed using immunohistochemistry according to previous studies [ 28 , 29 ]. Cx43 was mainly localized in the granulosa cell (Figures 4(a) – 4(e) ), and Cx37 was mainly localized in the oocyte and granulosa cell (Figures 5(a) – 5(e) ).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Localization of Cx43 and Cx37 was confirmed using immunohistochemistry according to previous studies [ 28 , 29 ]. Cx43 was mainly localized in the granulosa cell (Figures 4(a) – 4(e) ), and Cx37 was mainly localized in the oocyte and granulosa cell (Figures 5(a) – 5(e) ).…”
Section: Resultsmentioning
confidence: 87%
“…Immunohistochemistry was performed according to previous methods [ 28 , 29 ]. Briefly, after dehydration, antigen retrieval was performed in citrate buffer (pH 6.0) by treating the samples twice in a microwave oven at 100°C for 15 min; then, the slides were washed three times with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…However, the function of CREBRF is minimally characterized, so the mechanisms by which rs373863828 affects these phenotypes are currently unclear. Individual studies have indicated that this transcription factor impacts glucocorticoid signaling, autophagy, unfolded protein response, and starvation resistance, as well as murine decidualization, embryo implantation, and maternal behavior (Audas, Li, Liang, & Lu, 2008; Li et al, 2016; Martyn et al, 2012; Minster et al, 2016; Xue et al, 2016; Yang et al, 2013). Future studies should aim to refine the effect of this variation on the related phenotypes of height, weight, and BMI in other Pacific Island populations, as well as other anthropometric traits.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the knowledge on the role of LRF in pregnancy is scarce. Only one study has been published 34 , reporting the expression of LRF specifically at implantation sites in mouse uterus, low levels of LRF in uteri of mice with delayed implantation and a cross-talk of LRF with steroid hormones such as progesterone and estradiol.…”
Section: Discussionmentioning
confidence: 99%